Lithium ion battery and electric device

By optimizing the particle size distribution and interface stability of the positive and negative electrode material particles of lithium-ion batteries, the problem of uneven lithium-ion layers embedded in lithium and delimiting the material layer under the conditions of large-scale charging and discharge of lithium-ion batteries is solved, and the high cycle performance and safety of the battery are achieved.

CN119742417APending Publication Date: 2025-04-01JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411919985.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Under the conditions of large-scale charging and discharging of lithium ions, the transmission and migration of lithium ions are not timely, resulting in uneven lithium-ion layers on the positive and negative electrode sheets embedded in lithium and deliquification, causing cracking of the material layer, and the electrolyte reaction to generate by-products, damaging electrochemical properties, deteriorating cycle stability and creating safety hazards.

Method used

By optimizing the particle size distribution of positive electrode material particles and negative electrode material particles, the interface stability of the positive electrode sheet and negative electrode sheet are enhanced, the relationship between the particle size of positive electrode material particles and the depth of invasion of F elements is restricted, the proportion of invasion of F elements in the negative electrode material particles is limited, and the structural strength and uniformity of the positive and negative electrode active material layers are improved.

Benefits of technology

Effectively inhibit the side reaction between the inner positive electrode material particles and the electrolyte, reduce the probability of cracking, delay the inactivation of positive and negative electrode active materials, and improve the circulation performance and service life of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742417A_ABST
    Figure CN119742417A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery and a power utilization device, the lithium ion battery comprises a positive plate, a diaphragm, a negative plate and an electrolyte, the surface of the positive plate is covered with a positive active material layer comprising positive material particles, and the surface of the negative plate is covered with a negative active material layer comprising negative material particles; when the first capacity retention ratio of the battery is measured to be x, and x is greater than or equal to 78% and less than or equal to 89%, the diameter of the positive electrode material particles is D, the depth of an F element invasion layer of the positive electrode material particles is L, the thickness ratio m of the F element invasion layer is obtained to be equal to L / D, and m is less than or equal to 1-x; and counting the proportion n of the negative electrode material particles invaded by the F element in the negative electrode material particles, wherein n is less than or equal to (1-x) / 2. The particle size distribution of positive electrode material particles and negative electrode material particles is optimized, the interface stability of positive and negative electrode plates is enhanced, the side reaction with electrolyte is inhibited, and the high-rate cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrical devices, and in particular to a lithium-ion battery and an electrical device. Background Art

[0002] Lithium-ion batteries play a vital role in portable devices, electric vehicles and renewable energy storage systems due to their excellent energy storage capacity and wide range of applications. However, as application demand grows, the performance requirements for lithium-ion batteries are also getting higher and higher, such as maintaining high energy density and high-rate charge and discharge capabilities while achieving longer cycle life and greater safety.

[0003] In the electrochemical system of existing lithium-ion batteries, lithium ions are charged by escaping from the lattice of the positive electrode active material, passing through the separator via the electrolyte, and then embedding into the lattice of the negative electrode active material; lithium ions are discharged by escaping from the lattice of the negative electrode active material, passing through the separator via the electrolyte, and then embedding into the lattice of the positive electrode active material.

[0004] However, under high-rate charge and discharge conditions of lithium-ion batteries, the transfer and migration of lithium ions is often not timely enough, which will cause uneven lithium insertion and removal of the active material layers on the positive and negative electrodes, resulting in asymmetric stress on the surface particles of the active material layer and cracking. The electrolyte will invade the inner layer of the active material layer from the cracks of the surface particles and react with the particles in the inner layer to generate a large number of by-products, destroying the electrochemical properties of the active material layer, causing irreversible damage to the battery capacity, deteriorating the battery's cycle stability, and even causing safety hazards. Summary of the invention

[0005] In order to solve the above problems, optimize the particle size distribution of positive electrode material particles and negative electrode material particles, and enhance the interface stability of positive electrode sheets and negative electrode sheets, the first aspect of the present application provides a lithium ion battery, including a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte for transmitting lithium ions, the surface of the positive electrode sheet is covered with a positive electrode active material layer including positive electrode material particles, and the surface of the negative electrode sheet is covered with a negative electrode active material layer including negative electrode material particles. When the first capacity retention rate of the lithium ion battery is measured to be x, 78%≤x≤89%, the diameter of the positive electrode material particles is D, and the depth of the F element intrusion layer of the positive electrode material particles is L, and the thickness proportion m of the F element intrusion layer in the radial direction of the positive electrode material particles is obtained = L / D, and the thickness proportion m of the F element and the first capacity retention rate x also satisfy: m≤1-x; and

[0006] The proportion n of the negative electrode material particles invaded by the F element in the negative electrode material particles is counted, and satisfies: n≤(1-x) / 2.

[0007] By optimizing the particle size distribution of the positive electrode material particles and constraining the particle size of the positive electrode material particles and the penetration depth of the F element, the structural strength of the surface layer of the positive electrode active material layer in contact with the electrolyte is improved, so as to improve the tolerance to local stress caused by uneven lithium insertion and / or lithium deintercalation, reduce the probability of cracking, and effectively inhibit the side reaction between the positive electrode material particles in the inner layer and the electrolyte; on the other hand, the proportion of negative electrode material particles invaded by the F element in the negative electrode material particles is constrained, the uniformity of the negative electrode active material layer is improved, the local accumulation of lithium ions is avoided, the deactivation of the positive and negative electrode active materials is delayed, and the cycle performance of the lithium-ion battery is improved.

[0008] In some optional embodiments, when the lithium ion battery is cyclically charged and discharged at a 2C charge rate and a 5C discharge rate to reach a first capacity retention rate of x, the following test is performed:

[0009] The lithium-ion battery after cyclic charge and discharge is placed at 25° C., discharged at a rate of 0.2C to a discharge cut-off voltage of 2.5V, and after standing for 0.5 hours, the lithium-ion battery is disassembled and the positive electrode sheet and the negative electrode sheet are obtained and a cross section is prepared, and observation is performed using a SEM, and at a magnification of 1000 times, an EDS signal is photographed and collected to obtain a surface scan distribution map of the F element;

[0010] For the surface scan distribution diagram of the cross section of the positive electrode sheet: select no less than 100 positive electrode material particles from left to right and from top to bottom, and calculate the average diameter D of all the positive electrode material particles selected and the average thickness L of the F element invasion layer in its radial direction to obtain m;

[0011] For the surface scan distribution diagram of the cross-section of the negative electrode sheet: select no less than 100 of the negative electrode material particles from left to right and from top to bottom, define the negative electrode material particles in which the F element area in a single negative electrode material particle is greater than 5% as the negative electrode material particles invaded by the F element, count the number of negative electrode material particles invaded by the F element in all the negative electrode material particles screened out, and calculate n.

[0012] According to the above experimental method, the measured data are highly accurate.

[0013] In some optional embodiments, the diaphragm is arranged between the above-mentioned positive electrode sheet and the negative electrode sheet, the positive electrode material particles contain high-nickel ternary material, and the peak intensity ratio I003 / I104 of the XRD diffraction peak of the positive electrode sheet is y, and the porosity of the diaphragm is η, satisfying: y≥0.3*(2-lnη). By constraining the relationship between the ratio of I003 / I104 in high-nickel ternary materials and the porosity of the diaphragm, in the scenario of high-rate application, the activity decay of the I104 crystal high-nickel ternary material will be faster than that of the I003 crystal high-nickel ternary material, that is, I003 / I104 will gradually increase, and the porosity of the diaphragm will gradually decrease during the application process, that is, the value of (2-Inη) will gradually increase, wherein the rate of reduction of the porosity is positively correlated with the degree of interfacial side reactions of the positive and negative electrode material particles. The I003 / I104 ratio y≥0.3*(2-lnη) is limited to control the rate of reduction of the porosity of the diaphragm to adapt to the composition of the positive electrode material particles, so as to avoid a sharp decrease in porosity when applied at a high rate, thereby improving the uniformity of lithium insertion / deintercalation at the positive electrode interface and further optimizing the high-rate cycle performance and safety performance of the battery.

[0014] In some optional embodiments, the ratio y of I003 / I104 and the porosity η further satisfy: y≥0.5*(2-lnη)

[0015] In some optional embodiments, the method for testing the XRD diffraction peak of the positive electrode sheet of the lithium ion battery and the porosity η of the diaphragm includes:

[0016] S1: Take one of the lithium-ion batteries, place it at 25° C. for more than 2 hours, and discharge it at a rate of 0.2C to a discharge cut-off voltage of 2.5V, then let it stand for 10 minutes, and disassemble it to obtain the positive electrode sheet and the separator;

[0017] S2: After washing the positive electrode sheet and the separator with dimethyl carbonate three times, the positive electrode sheet and the separator were placed in a vacuum oven at 60° C. and baked for 2 h;

[0018] S3: taking out the positive electrode sheet and the separator and waiting for them to cool down;

[0019] S4: testing the positive electrode sheet by XRD to obtain a diffraction peak spectrum of the positive electrode sheet, and calculating a ratio of peak intensity ratio I003 / I104; and

[0020] S5: Take the diaphragm and test to obtain the porosity η.

[0021] In some optional embodiments, when the first capacity retention rate of the lithium ion battery is x, the porosity of the diaphragm corresponds to η x , and also satisfies: x*y≥0.3*(2-lnη x ).

[0022] In some optional embodiments, the lithium salt concentration of the electrolyte is E mol / L, and after the lithium-ion battery is discharged at a rate of 0.2C to a discharge cut-off voltage of 2.5V, the negative electrode sheet is taken out and an XRD test is performed to obtain a test spectrum, and the highest peak and the second highest peak in the test spectrum are selected, and the ratio of the peak intensity of the highest peak to the peak intensity of the second highest peak is P, and satisfies: 3P / 2≥E≥P / 6. The diffraction peaks in the XRD diffraction peak spectrum of the negative electrode sheet respectively represent a crystal form in the negative electrode material particles, where the ratio of the peak intensity of the highest peak to the peak intensity of the second highest peak reflects the stability of the negative electrode material particles to a certain extent. The higher the stability of the negative electrode material particles, the weaker the kinetic performance of the lithium ion migration is. The higher the lithium salt concentration of the electrolyte, the faster the migration rate of lithium ions. The lithium salt concentration E and the ratio P of the highest peak intensity to the second highest peak intensity of the negative electrode sheet are controlled to be: 3P / 2≥E≥P / 6, which can balance the stability and kinetic performance of the negative electrode sheet. The negative electrode sheet can efficiently and persistently complete the insertion and deinsertion reactions of large-flux lithium ions, ensure that the interface stability and rate performance of the negative electrode sheet are in the optimal range, and achieve the optimal rate performance of the battery.

[0023] In some optional embodiments, the positive electrode material particles located on the surface of the positive electrode active material layer are further doped with element Z, and the element Z is one or more of Al, B, Zr, Ti, Ba, Mn, Co, Y, La, Ca, Sr and Sb. The above chemical elements are doped in the positive electrode material particles to improve the structural stability of the positive electrode active material.

[0024] In some optional embodiments, the weight percentage of the element Z in the positive electrode material particles located on the surface layer is 0.05%-2%.

[0025] The second aspect of the present application provides an electric device, including the lithium-ion battery described above. Since the lithium-ion battery has the above-mentioned beneficial effects, the electric device provided by the present application has good structural stability of the positive and negative active material layers during high-power charging and discharging, effectively suppresses electrolyte side reactions, improves the battery's cycle performance, and prolongs the service life of the electric device. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0027] Figure 1 is a schematic structural diagram of a lithium-ion battery of an optional embodiment of the present application;

[0028] Figure 2 This is a schematic structural diagram of a positive electrode sheet, a separator, and a negative electrode sheet after a roll core portion of a lithium-ion battery in an optional embodiment of the present application is unfolded;

[0029] Figure 3 It is a structural schematic diagram of a longitudinal cross-section of a roll core of a lithium-ion battery according to an optional embodiment of the present application.

[0030] Figure numerals: 2-winding core, 21-positive electrode sheet, 212-positive electrode current collector, 210-positive electrode active material layer, 2101-positive electrode material particles, 23-separator, 25-negative electrode sheet, 252-negative electrode current collector, 250-negative electrode active material layer, 2501-negative electrode material particles, 3-electrolyte. DETAILED DESCRIPTION

[0031] Embodiments of the present embodiment are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present embodiment, and should not be construed as limiting the present embodiment.

[0032] In the description of this embodiment, it should be understood that descriptions involving orientation, such as up, down, front, back, left, right, etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing this embodiment and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on this embodiment.

[0033] In the description of this embodiment, "several" means one or more, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0034] In the description of this embodiment, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in this embodiment based on the specific content of the technical solution.

[0035] The common structure of an existing lithium-ion battery includes a shell with an opening at one end, a winding core 2 assembled in the shell from the opening, an electrolyte 3 injected into the shell, and a cap covering the shell opening. It is understandable that the lithium-ion battery can be a cylindrical lithium-ion battery or a square lithium-ion battery.

[0036] Please refer to Figure 1-Figure 3 , Figure 1 A schematic diagram of the structure of a lithium-ion battery according to an embodiment of the present application is shown. Figure 2 The schematic diagram of the three-dimensional structure after the core part is unfolded is shown. Figure 3 The cross-section of the positive electrode sheet and the negative electrode sheet is shown, wherein Figure 2 The winding core 2 is formed by winding the stacked positive electrode sheet 21, the separator 23 and the negative electrode sheet 25, see Figure 3 The positive electrode sheet 21 includes a positive electrode current collector 212 and a positive electrode active material layer 210 coated on both sides of the positive electrode current collector 212, and the negative electrode sheet 25 includes a negative electrode current collector 252 and a negative electrode active material layer 250 coated on both sides of the negative electrode current collector 252, and the thickness of the active material coating is greater than the thickness of the current collector. The charged particles in the electrolyte 3 undergo insertion or deinsertion reactions on the surfaces of the positive electrode active material layer 210 and the negative electrode active material layer 250.

[0037] In a first aspect, the present application provides a lithium-ion battery, comprising a positive electrode sheet 21, a separator 23, a negative electrode sheet 25 and an electrolyte 3 for transmitting lithium ions, wherein the surface of the positive electrode sheet 21 is covered with a positive electrode active material layer 210 comprising positive electrode material particles 2101, and the surface of the negative electrode sheet 25 is covered with a negative electrode active material layer 251 comprising negative electrode material particles 2501.

[0038] Take a lithium ion battery, and charge and discharge it cyclically at a 2C charge rate and a 5C discharge rate to reach a first capacity retention rate x, 78%≤x≤89%;

[0039] The test method of the first capacity retention rate x is:

[0040] Take a lithium ion battery prepared according to any of the above embodiments, place it in a 25°C constant temperature box for more than 4 hours, and test it according to the following steps:

[0041] S01: The battery is charged at a constant current of 2C to 4.2V, and charged at a constant voltage to a current of 0.025C, and left to stand for 15 minutes; the battery is discharged at a constant current of 5C to 2.5V, and left to stand for 30 minutes;

[0042] S02: Repeat the above step S01 N times (2≤N≤2000); record the first discharge capacity as the initial capacity, recorded as a1, and record the discharge capacity at the Nth cycle, recorded as b1;

[0043] S03: When b1 / a1×100% is within the x value range, perform the following test:

[0044] S11: The lithium-ion battery after the above cyclic charge and discharge is placed at 25°C and discharged at a rate of 0.2C to a discharge cut-off voltage of 2.5V. After standing for 0.5 hours, the lithium-ion battery is disassembled to obtain the positive electrode sheet 21 and the negative electrode sheet 25 and a cross section is prepared. Figure 3 , using SEM to observe, and at a magnification of 1000 times, photographing and collecting EDS signals to obtain the surface scan distribution map of F element;

[0045] For the surface scan distribution diagram of the cross section of the positive electrode sheet 21: from left to right and from top to bottom, select no less than 100 positive electrode material particles 2101 in sequence, and count the average diameter D of all the positive electrode material particles 2101 selected and the average thickness L of the F element intrusion layer in the radial direction thereof, and calculate the thickness ratio m=L / D of the F element intrusion layer in the radial direction of the positive electrode material particles 2101;

[0046] For the surface scan distribution diagram of the cross section of the negative electrode sheet 25: from left to right and from top to bottom, select no less than 100 negative electrode material particles 2501 in sequence, define the negative electrode material particles 2501 in which the F element area accounts for more than 5% in a single negative electrode material particle 2501 as the negative electrode material particles 2501 invaded by the F element, count the number of the negative electrode material particles 2501 invaded by the F element in all the negative electrode material particles 2501 screened out, and calculate the proportion n of the negative electrode material particles 2501 invaded by the F element in all the negative electrode material particles 2501 screened out;

[0047] Furthermore, the thickness ratio m of the F element and the capacity retention rate x are limited to satisfy: m≤1-x; and

[0048] Furthermore, it is defined that the proportion n of the negative electrode material particles 2501 invaded by the F element in the negative electrode material particles 2501 satisfies: n≤(1-x) / 2.

[0049] It should be noted that a CEI film (Cathode Electrolyte Interphase, a passivation film formed when the positive electrode material in a lithium-ion battery contacts the electrolyte 3) is formed at the interface where the positive electrode active material layer 210 contacts the electrolyte 3, and a SEI film (Solid Electrolyte Interface, a passivation layer covering the surface of the negative electrode material formed during the first charge and discharge process of a lithium-ion battery) is formed at the interface where the negative electrode active material layer 251 contacts the electrolyte 3; the stability of the CEI film and the SEI film is the interface stability of the positive electrode sheet 21 and the negative electrode sheet 25. Specifically, the content of F element in the positive electrode active material layer 210 and the negative electrode active material layer 251 can be used to evaluate the interface stability of the positive and negative electrode sheets. The specific principle is: F element is the most electronegative element, the chemical properties of fluoride are stable, and a protective layer is formed on the surface of the positive and negative electrodes of the battery, which inertly protects the active substances in the electrolyte 3, thereby preventing the continuous decomposition of the electrolyte 3 and reducing the risk of thermal runaway and safety hazards of the battery. It can be understood that the depth L of the F element invasion layer of the positive electrode material particles 2101 and the proportion of the F element invading the negative electrode material particles 2501 exceeding 5% of the area can be used to measure the content of F element at the interface of the positive and negative electrode sheets, and the degree of interaction between F element and the positive electrode material particles 2101 or the negative electrode material particles 2501 is further limited, which can more accurately reflect the content of F element that has a passivation effect on the electrolyte 3, and therefore, there is more confidence in the technical effect achieved.

[0050] See also Figure 3 By optimizing the particle size distribution of the positive electrode material particles 2101 and constraining the particle size of the positive electrode material particles 2101 and the depth of the F element penetration layer, the interface structure strength of the positive electrode active material layer 210 in contact with the electrolyte 3 is improved, so as to improve the tolerance to local stress caused by uneven lithium insertion and / or lithium deintercalation, reduce the probability of cracking, and effectively inhibit the side reaction between the inner layer of the positive electrode material particles 2101 and the electrolyte 3; on the other hand, the proportion of the negative electrode material particles 2501 invaded by the F element in the negative electrode material particles 2501 is constrained, the uniformity of the negative electrode active material layer 251 is improved, the local accumulation of lithium ions is avoided, the deactivation of the positive and negative electrode active materials is delayed, and the cycle performance of the lithium ion battery is improved.

[0051] In some alternative embodiments, see Figure 2 and Figure 3The diaphragm 23 is arranged between the positive electrode sheet 21 and the negative electrode sheet 25, the positive electrode material particles 2101 contain high-nickel ternary materials, and the peak intensity ratio I003 / I104 of the XRD diffraction peak in the positive electrode sheet is y, and the porosity of the diaphragm 23 is η, satisfying: y≥0.3*(2-lnη). Through the relationship between the peak intensity ratio I003 / I104 of the XRD diffraction peak in the positive electrode sheet and the porosity of the diaphragm 23, in the scenario of high-rate application, the activity decay of the I104 crystal high-nickel ternary material will be faster than that of the I003 crystal high-nickel ternary material, that is, I003 / I104 will gradually increase, and the porosity of the diaphragm 23 will gradually decrease during the application process, that is, the value of (2-lnη) will gradually increase, wherein the rate of reduction of the porosity is positively correlated with the degree of interfacial side reactions of the positive and negative electrode sheets, and the ratio of I003 / I104 is limited to y≥0.3*(2-lnη) to control the rate of reduction of the porosity of the diaphragm 23 to adapt to the composition of the positive electrode material particles 2101, and to prevent the porosity from decreasing sharply when applied at a high rate, thereby improving the uniformity of lithium insertion / deintercalation at the interface of the positive electrode sheet 21, and further optimizing the high-rate cycle performance and safety performance of the battery. It should be noted that the peak intensity ratio I003 / I104 of the positive electrode sheet and the peak intensity ratio of the negative electrode sheet are obtained by testing according to the general rules of X-ray diffraction analysis and the lattice parameter determination method of graphite JIS K 0131-1996 and JB / T4220-2011.

[0052] Specifically, the test method of the XRD diffraction peak of the positive electrode sheet 21 and the porosity η of the diaphragm of the lithium-ion battery includes:

[0053] S1: Take a fresh lithium-ion battery, place it at 25° C. for more than 2 hours, and discharge it at a rate of 0.2C to a discharge cut-off voltage of 2.5V, then let it stand for 10 minutes, and disassemble it to obtain the positive electrode sheet 21 and the separator 23;

[0054] S2: After washing the positive electrode sheet 21 and the separator 23 with dimethyl carbonate three times, the positive electrode sheet 21 and the separator 23 are placed in a vacuum oven at 60° C. and baked for 2 hours; and

[0055] S3: Take out the positive electrode sheet 21 and the separator 23 and wait for them to cool down;

[0056] S4: testing the positive electrode sheet 21 by XRD, obtaining a diffraction peak spectrum of the positive electrode sheet 21, and calculating a ratio of a peak intensity ratio I003 / I104; and

[0057] S5: Take the diaphragm 23 and test to obtain the porosity η (the test method refers to the national standard GB / T36363-2018).

[0058] It is understandable that in high-rate application scenarios, the porosity of the diaphragm 23 will gradually decrease, while the active materials on the positive and negative electrode sheets will gradually inactivate. Furthermore, the ratio y of I003 / I104 and the porosity η further satisfy: y≥0.5*(2-lnη), further constraining the rate of change of the porosity of the diaphragm 23, adapting to the lithium insertion and delithiation activity of the positive electrode material particles 2101, so that during high-rate application, the rate of lithium ions passing through the diaphragm 23 matches the rate of lithium insertion or deintercalation at the interface of the positive electrode sheet 21, thereby avoiding the local accumulation of lithium ions in the positive electrode sheet 21, reducing the risk of cracking, and inhibiting the occurrence of side reactions.

[0059] In some optional embodiments, when the first capacity retention rate of the lithium ion battery is x, the porosity of the diaphragm 23 corresponds to η. x , and also satisfies: x*y≥0.3*(2-lnη x ). The porosity of the diaphragm 23 is matched with the capacity retention rate of the battery, so that in a high-rate application scenario, the predetermined capacity retention rate can still be maintained, that is, the cycle performance of the battery is improved and the battery life is extended.

[0060] In some optional embodiments, the lithium salt concentration of the electrolyte 3 is E mol / L, the lithium ion battery is discharged at a rate of 0.2C to a discharge cut-off voltage of 2.5V, the negative electrode sheet 25 is taken out and an XRD test is performed to obtain a test spectrum, the highest peak and the second highest peak in the test spectrum are selected, the ratio of the peak intensity of the highest peak to the peak intensity of the second highest peak is P, and satisfies: 3P / 2≥E≥P / 6. The diffraction peaks in the XRD diffraction peak test spectrum of the negative electrode sheet 25 respectively represent a crystal form in the negative electrode material particles 2501, wherein the ratio of the peak intensity of the highest peak to the peak intensity of the second highest peak reflects the stability of the negative electrode material particles 2501 to a certain extent. The higher the stability of the negative electrode material particles 2501, the weaker the kinetic performance of the lithium ion migration is. The higher the lithium salt concentration of the electrolyte 3, the faster the migration rate of the lithium ions. The lithium salt concentration E and the ratio P of the peak intensity of the highest peak to the peak intensity of the second highest peak of the negative electrode sheet 25 are controlled to be: 3P / 2≥E≥P / 6, which can balance the stability and kinetic performance of the negative electrode sheet 25. The negative electrode sheet 25 can efficiently and persistently complete the insertion and deinsertion reactions of large flux lithium ions, ensure that the interface stability and rate performance of the negative electrode sheet 25 are in the optimal range, and achieve the optimal rate performance of the battery.

[0061] In some alternative embodiments, see Figure 3The positive electrode material particles 2101 located on the surface of the positive electrode active material layer 210 are also doped with element Z, and the element Z is one or more of Al, B, Zr, Ti, Ba, Mn, Co, Y, La, Ca, Sr and Sb. The above chemical elements are doped in the positive electrode material particles 2101 to improve the structural stability of the positive electrode active material. Specifically, the above chemical elements are doped on the surface of the positive electrode material particles 2101 to form physical isolation protection to reduce the side reaction between the positive electrode active material layer 210 and the electrolyte 3.

[0062] In some alternative embodiments, see Figure 3 , the weight percentage of the element Z in the positive electrode material particles 2101 located on the surface layer is 0.05%-2%. By doping the element Z with an appropriate content, on the one hand, it cooperates with the F element to form a passivation layer to improve the interface stability of the positive electrode active material layer 210; on the other hand, it reduces the impact on the content of energy storage substances in the positive electrode active material to ensure the battery capacity.

[0063] The second aspect of the present application provides an electric device, including the above-mentioned lithium-ion battery. Since the lithium-ion battery has the above-mentioned beneficial effects, the electric device provided by the present application has good structural stability of the positive and negative active material layers during high-power charging and discharging, effectively inhibits the electrolyte 3 side reactions, improves the battery's cycle performance, and prolongs the service life of the electric device.

[0064] The technical solution of the present application is described below in conjunction with Examples 1-9 and Comparative Examples 1-5.

[0065]

[0066]

[0067] The above Examples 1-9 and Comparative Examples 1-5 were subjected to 600-cycle cycle retention test, hot box test and EDS element analysis test respectively:

[0068] The test method for 600-cycle cycle retention rate is:

[0069] Take a lithium ion battery prepared according to any of the above embodiments, place it in a 25°C constant temperature box for more than 4 hours, and test it according to the following steps:

[0070] S31: The battery is charged at a constant current of 3C to 4.2V, and charged at a constant voltage to a current of 0.025C, and left to stand for 15 minutes; the battery is discharged at a constant current of 10C to 2.5V, and left to stand for 30 minutes; the first cycle discharge capacity is recorded as the initial capacity and recorded as a;

[0071] S32: repeat the above step S31 600 times; record the discharge capacity at the 600th cycle, denoted as b;

[0072] S33: Calculate the 600-cycle cycle retention rate as b / a×100%.

[0073] The hot box test method is:

[0074] Take a lithium ion battery prepared according to any of the above embodiments, and after 500 cycles of charge and discharge, place the battery in a 25°C constant temperature box for more than 4 hours and test it according to the following steps:

[0075] S41: The battery is discharged at a constant current of 0.1C discharge rate to 2.5V cut-off, and left to stand for 5 minutes;

[0076] S42: The battery is charged at a constant current of 0.2C to a cutoff of 4.2V, and at a constant voltage of 0.05C to a cutoff, and allowed to stand for 5 minutes;

[0077] S43: Place the battery in a heating box, set the heating rate to 5K / min, heat to 130°C, and keep it for 1 hour, then stop heating and cool it to below 30°C by self-heating;

[0078] S44: If the battery does not catch fire or emit smoke, it is considered to have passed; otherwise, it is considered to have failed. At least 6 batteries are tested in parallel for one embodiment or comparative example, and the pass rate is recorded.

[0079] The qualitative and / or quantitative analysis of the above element Z is carried out by energy dispersive spectroscopy (EDS).

[0080] The EDS element analysis method is:

[0081] S51: preparing a cross-section sample of the positive electrode sheet 21 or the negative electrode sheet 25;

[0082] S52: Check the working environment of the EDS detector and calibrate the EDS system;

[0083] S53: Sample loading, collecting the EDS spectrum of the sample to be tested under predetermined electron beam conditions.

[0084] S54: Use EDS analysis software to process and analyze the collected spectra to obtain the types and contents of the elements.

[0085] Examples 1-2 and Comparative Example 1 are control groups with the particle size D of the positive electrode material particles 2101 and the penetration depth L of the F element as variables, Examples 1 and 3 and Comparative Examples 2-3 are control groups with the penetration ratio of the F element in the negative electrode material particles 2501 as variables, Example 4 and Comparative Example 4 are control groups with the ratio of I003 / I104 in the positive electrode material particles 2101 as variables, Examples 5-6 and Comparative Example 5 are control groups with the crystal structure of the negative electrode sheet 25 and the lithium salt concentration in the electrolyte 3 as variables, Examples 7-8 are control groups with the porosity as variables, and Examples 7-9 are control groups with the type of doping element Z as a variable. Specific comparison results are shown in Tables 1 to 5:

[0086] Table 1

[0087]

[0088] It can be seen from Table 1 that the ratio m of the radial depth L of the F element invading the positive electrode material particles 2101 to the particle size D of the positive electrode material particles 2101 can significantly affect the cycle performance and safety of the battery. Among them, when m≤1-x, the cycle retention rate is relatively higher. At the same time, the n value of the negative electrode material particles 2501 is guaranteed to be n≤(1-x) / 2, and the cycle retention rate is better. When m>1-x, the cycle retention rate of the battery is poor and the safety of use is poor, and the pass rate of the temperature chamber test drops to 0.

[0089] Table 2

[0090]

[0091] It can be seen from Table 2 that the proportion of particles in the negative electrode material particles 2501 with an area of ​​more than 5% invaded by the F element has a greater influence on the cycle retention rate of the battery. Among them, the proportion of F element invading the negative electrode material particles 2501 is n≤(1-x) / 2, and the higher the cycle retention rate of the battery, when n>(1-x) / 2, the cycle retention rate of the battery will decrease relatively, and the decline will increase with the increase of the difference between n and (1-x) / 2. Among them, when the difference between n and (1-x) / 2 reaches 4.5 or above, the cycle retention rate falls below 60%, and the safety also decreases significantly. The pass rate of the temperature chamber test is 0. In the actual production process, the proportion of F element invading the negative electrode material particles 2501 is preferably about 7%.

[0092] Table 3:

[0093]

[0094]

[0095] It can be seen from Table 3 that the ratio y of the two crystal forms I003 / I104 in the positive electrode material particles 2101 has a certain influence on the cycle performance of the battery. When y≥0.3*(2-lnη), or further y≥0.5*(2-lnη), the cycle performance is good, and further, when x*y≥0.3*(2-lnη), the safety performance is guaranteed.

[0096] Table 4:

[0097]

[0098] It can be seen from Table 4 that the lithium salt concentration E in the electrolyte 3 has a great influence on the cycle performance and safety performance of the battery. Among them, when 3P / 2≥E≥P / 6, that is, 0.16≤E / P≤1.5, the cycle retention rate and safety test pass rate of the battery are relatively high.

[0099] Table 5:

[0100]

[0101] It can be seen from Table 5 that the type of doping element Z has little effect on the cycle retention rate of the battery, and the preferred chemical element is Zr; specifically, the content of element Z has little effect on the cycle retention rate and safety performance of the battery. The porosity η of the separator 23 alone has little effect on the cycle performance and safety of the battery.

[0102] In summary, the present application, on the one hand, can effectively enhance the structural stability of the interface between the positive and negative electrode sheets and the electrolyte 3, reduce the probability of cracking, and inhibit the occurrence of side reactions by constraining the cross-linking effect between the positive electrode material particles 2101 and the negative electrode material particles 2501 of the positive and negative electrode sheets; on the other hand, the crystal form of the positive electrode material particles 2101 and the crystal form of the negative electrode material particles 2501 are controlled at the microscopic level to enhance their ability to insert and extract lithium ions to meet the needs of high-rate applications of the battery; on the third hand, the porosity of the diaphragm 23 is limited to match the activity of the positive and negative electrode material particles 2501, to achieve orderly conduction of lithium ions, avoid local accumulation to form stress, further reduce the risk of interface cracking, and inhibit the occurrence of side reactions. And finally achieve high-rate operation and high cycle performance of lithium-ion batteries, while also ensuring the safety of use.

[0103] In the description of this specification, reference to the terms "some embodiments", "an example", or similar descriptions means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment are included in at least one embodiment or example. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0104] Although examples of the present embodiment have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present embodiment, and the scope of the present embodiment is defined by the claims and their equivalents.

Claims

1. A lithium-ion battery, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte for transmitting lithium ions, wherein the surface of the positive electrode sheet is covered with a positive electrode active material layer comprising positive electrode material particles, and the surface of the negative electrode sheet is covered with a negative electrode active material layer comprising negative electrode material particles, characterized in that: When the first capacity retention rate of the lithium-ion battery is measured to be x, 78%≤x≤89%, the diameter of the positive electrode material particle is D, and the depth of the F element invasion layer of the positive electrode material particle is L, the thickness ratio of the F element invasion layer in the radial direction of the positive electrode material particle is m=L / D, and the thickness ratio m of the F element invasion layer and the first capacity retention rate x also satisfy: m≤1-x; and The proportion n of the negative electrode material particles invaded by the F element in the negative electrode material particles is counted, and satisfies: n≤(1-x) / 2.

2. The lithium-ion battery according to claim 1, characterized in that The lithium ion battery is subjected to the following test when the first capacity retention rate is x after cyclic charge and discharge at a 2C charge rate and a 5C discharge rate: The lithium-ion battery after cyclic charge and discharge is placed at 25° C., discharged at a rate of 0.2C to a discharge cut-off voltage of 2.5V, and after standing for 0.5 hours, the lithium-ion battery is disassembled and the positive electrode sheet and the negative electrode sheet are obtained and a cross section is prepared, and observation is performed using a SEM, and at a magnification of 1000 times, an EDS signal is photographed and collected to obtain a surface scan distribution map of the F element; For the surface scan distribution diagram of the cross section of the positive electrode sheet: select no less than 100 positive electrode material particles from left to right and from top to bottom, and calculate the average diameter D of all the positive electrode material particles selected and the average thickness L of the F element invasion layer in its radial direction to obtain m; For the surface scan distribution diagram of the cross-section of the negative electrode sheet: select no less than 100 of the negative electrode material particles from left to right and from top to bottom, define the negative electrode material particles in which the F element area in a single negative electrode material particle is greater than 5% as the negative electrode material particles invaded by the F element, count the number of negative electrode material particles invaded by the F element in all the negative electrode material particles screened out, and calculate n.

3. The lithium-ion battery according to claim 1, characterized in that The diaphragm is arranged between the positive electrode sheet and the negative electrode sheet, the positive electrode material particles contain high-nickel ternary material, and the peak intensity ratio I003 / I104 of the XRD diffraction peak of the positive electrode sheet is y, and the porosity of the diaphragm is η, satisfying: y≥0.3*(2-lnη).

4. The lithium-ion battery according to claim 3, characterized in that: The ratio y of I003 / I104 and the porosity η further satisfy: y≥0.5*(2-lnη).

5. The lithium ion battery according to claim 3 or 4, characterized in that: The method for testing the XRD diffraction peak of the positive electrode sheet and the porosity η of the diaphragm of the lithium ion battery includes: S1: Take one of the lithium-ion batteries, place it at 25° C. for more than 2 hours, and discharge it at a rate of 0.2C to a discharge cut-off voltage of 2.5V, then let it stand for 10 minutes, and disassemble it to obtain the positive electrode sheet and the separator; S2: After washing the positive electrode sheet and the separator with dimethyl carbonate three times, the positive electrode sheet and the separator were placed in a vacuum oven at 60° C. and baked for 2 h; S3: taking out the positive electrode sheet and the separator and waiting for them to cool down; S4: testing the positive electrode sheet by XRD to obtain a diffraction peak spectrum of the positive electrode sheet, and calculating a ratio of peak intensity ratio I003 / I104; and S5: Take the diaphragm and test to obtain the porosity η.

6. The lithium ion battery according to claim 3, characterized in that: When the first capacity retention rate of the lithium ion battery is x, the porosity of the diaphragm corresponds to η x , and also satisfies: x*y≥0.3*(2-lnη x ).

7. The lithium-ion battery according to claim 1, characterized in that: The lithium salt concentration of the electrolyte is E mol / L. After the lithium ion battery is discharged at a rate of 0.2C to a discharge cut-off voltage of 2.5V, the negative electrode sheet is taken out and an XRD test is performed to obtain a test spectrum. The highest peak and the second highest peak in the test spectrum are selected. The ratio of the peak intensity of the highest peak to the peak intensity of the second highest peak is P, and satisfies: 3P / 2≥E≥P / 6.

8. The lithium-ion battery according to claim 1, characterized in that The positive electrode material particles located on the surface of the positive electrode active material layer are also doped with element Z, and the element Z is one or more of Al, B, Zr, Ti, Ba, Mn, Co, Y, La, Ca, Sr and Sb.

9. The lithium-ion battery according to claim 8, characterized in that: The weight percentage of the element Z in the positive electrode material particles located on the surface layer is 0.05%-2%.

10. An electrical device, characterized in that: Comprising a lithium ion battery according to any one of claims 1 to 9.

Citation Information

Cited By

  • Lithium-ion battery and electrical apparatus

    WO2026138512A1